Relevance of Kautilya’s tax system in Modern Economy of Nepal - Dangal, Dil Nath (Curriculum Development Journal, 2020)
Taxes, usually regarded as an unpleasant subject, are compulsory levies for the general purposes of the government. The objective of this article is to make comparative study between Kautilya tax system and modern tax system of Nepal. For methodology that helps meet the objective of this study, historical and analytical research design has been used. Based on this objective and methodology, this study finds many concepts of Nepali-modern tax system are profoundly influenced by the tax system of Kautilya.